ROLE OF MICROORGANISMS IN THE SUPERGENE TRANSFORMATION OF POLYMETALLIC ORES AND THE FORMATION OF BIOGEOCHEMICAL ANOMALIES OF NOBLE METALS IN DEPOSITS OF TRANSBAIKALIA - Tatarinov A.V.; Yalovik L.I.; Danilova E.V.; Barkhutova D.D.; Prokopchuk S.I.; Zhmodik S.M. (My University, 2007)
Sulfide and sulfide–oxide ores of silver–lead–zinc deposits (Tarbagatai, Mykert-Sanzheev, and Dovatka) of the Dzhida–Vitim base metal belt confined to the Paleozoic–Mesozoic Uda–Vitim rift zone are characterized by high contents of Ag (up to 2990 g/t), platinum group metals (up to 12.3–74.6 g/t), and Au (up to 1.2 g/t). Oxidized ores are more enriched in noble metals than primary ores. It has also been established that, relative to incinerated samples of undecomposed wood, wood ash of decayed stumps of pine and larch growing above orebodies of the Mykert-Sanzheev deposit are characterized by the highest concentrations of Ag, Au, Pt, and Pd. For example, wood ash of decayed stumps, old crust, and decayed pine cone in the Mykert-Sanzheev deposit area is characterized by anomalously high concentrations of Ag (3000 g/t), Pt (5 g/t), Ru (230 mg/t), Au (190 mg/t), and Pd (60 mg/t), which are comparable with their concentrations in sphalerite-galena ores.